Advance control of Dual Active Bridge Multilevel Inverter (DABMI) with Open Winding Transformer (OWT) model - Bohari, Azuwien Aida (2021)
In recent years, Renewable Energy Sources (RES) are used to fulfil the growing demand for energy. The integration of RES into the grid incorporates power electronic converters for energy conversion. Voltage unbalance is one of the typical adverse grid disturbances commonly encountered in RES. Power quality (PQ) issues have turned out to be major problem and become extra prominent for users from all levels of usage as more nonlinear equipment are connected to the power grid. Using efficient energy conversion topologies by itself is inadequate in controlling system performance. In order to maintain and increase the system stability and reliability, Model Predictive Control (MPC) has been designed for Direct Power Control (DPC) namely Model Predictive Direct Power Control (MPDPC) which improves the PQ referral detection and reduces power ripple. Conservative Power Theory (CPT) has recently emerged to introduce new concepts concerning the definition of power and current terms. Consequently, this study proposed MPDPC of Dual Active Bridge Multilevel Inverter (DABMI) for grid connected application which incorporate the concept of CPT. The objectives of the proposed control approach is to improve the system performance during various conditions specifically for balanced and unbalanced grid voltage condition with two different cases of topology, namely DABMI and DABMI, with floating capacitor voltage. The ultimate goal of this study is to establish an advanced controller using MPDPC based CPT concept which improves steady state, transient state, Total Harmonic Distortion current (THDi) and lessens the power ripple. The complete DABMI along with the proposed MPDPC based CPT have been modeled in Matlab Simulink software and compared with the conventional and improved MPDPC. The simulation results show that the proposed approach manages to improve the system performance to achieve constant active and reactive power and at the same time produce the sinusoidal current under unbalanced testing condition with 0.56% of THDi for asymmetric DABMI topology and 1.12% of THDi for floating capacitor DABMI topology; those are below 5%, which is within the IEEE 519 standard.